Diversifikasi Pangan Melalui Pemanfaatan Sumberdaya Lokalâ€Uwiâ€ Sebagai Bahan Mie Instant - wuryantoro wuryantoro; Indah Rekyani Puspitawati (Universitas Merdeka Madiun, 2020)
Abstractâ€” Uwi plants (Dioscorea sp.) as one of the types of tuber plants have the potential to support food diversity and food security in the future because it is very tolerant to be planted on dry land with a huge potential in Indonesia. The research aims to obtain a variety of diversified foods based on uwi plants. The research method used a completely randomized design laboratory scale consisting of six treatments repeated three times. These factors are the various colors of tubers used as research material including dark yellow (orange), yellow, murky white, white, purple and purple spurt. Observations include texture, elasticity, aroma, colour and taste through organoleptic tests. Instant noodles and wet noodles are used as a comparison. The study was conducted in the Agronomy Laboratory of the Faculty of Agriculture, Merdeka University, Madiun, from October to December 2018. The results showed that compared to conventional noodles as a control, the appearance of colour, taste, texture and aroma of noodles after being cooked was not much different. Whereas seen from the elasticity of uwi noodles has a lower elasticity. The difference is also in the appearance of raw dried noodles, the color and aroma are still inferior to dry noodles and instant noodles. Thus, uwi flour is potential to be developed as a food ingredient, considering that uwi carbohydrates have a low glycemic index. Â Keywordsâ€”: food diversity; dry noodle; tuber color; uwi flour.